DISIPLIN KERJA PEGAWAI DI DINAS PENDIDIKAN KABUPATEN CIAMIS - Muhammad Fahra Alfania Zahra (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze and determine the level of work discipline of employees at the Ciamis Regency Education Office. Work discipline is an important factor that affects the achievement of organizational goals. However, initial observations show indications of a decline in discipline, such as a fairly high level of attrition and the existence of two work programs that do not reach the 100% target. The research design used is qualitative research with a descriptive approach. Primary data sources were obtained through interviews, while secondary data were obtained from literature and supporting documents. The informant selection technique used purposive sampling with a total of 8 informants. The results of the study show that the work discipline of employees at the Ciamis Regency Education Office in general is not optimal. Of the 8 dimensions of work discipline measured (based on Hasibuan), 6 dimensions have been implemented optimally, namely: Goals and abilities, Role models and leaders, Reciprocity, Justice, Inherent Supervision (Waskat), and Human Relations. Meanwhile, the 2 dimensions that were found to be not optimal and became obstacles were the dimensions of Punitive Sanctions and Firmness. The obstacles found include employees who enter the office during the day, go home early, and use working hours for unproductive activities (smoking, coffee, playing mobile phones). Efforts to overcome these obstacles include increasing Inherent Supervision (Waskat), the use of electronic presence equipped with photos of faces and office coordinates, cutting welfare from regional allowances, and affirming leadership in providing punitive sanctions to indisciplined employees.